2019
DOI: 10.2147/ijn.s203555
|View full text |Cite
|
Sign up to set email alerts
|

<p>Stimulus-responsive vesicular polymer nano-integrators for drug and gene delivery</p>

Abstract: Over the past two decades, nano-sized biosystems have increasingly been utilized to deliver various pharmaceutical agents to a specific region, organ or tissue for controllable precision therapy. Whether solid nanohydrogel, nanosphere, nanoparticle, nanosheet, micelles and lipoproteins, or “hollow” nanobubble, liposome, nanocapsule, and nanovesicle, all of them can exhibit outstanding loading and releasing capability as a drug vehicle – in particular polymeric nanovesicle, a microscopic hollow sphere that encl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…In addition, many previous reports showed that the β-thiopropionate linkage was not only cleaved by reductive stimuli but it could also be degraded by acidic conditions (Lv et al., 2014 ; Zou et al., 2014 ). It is well known that within normal tissue pH is ∼7.4, but within the lysosome and endosome the pH is ∼5–6 (Zou et al., 2014 ; Mu et al., 2019 ). Thereby, U-SS-M may degrade in cell lysosome and endosome acidic condition.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many previous reports showed that the β-thiopropionate linkage was not only cleaved by reductive stimuli but it could also be degraded by acidic conditions (Lv et al., 2014 ; Zou et al., 2014 ). It is well known that within normal tissue pH is ∼7.4, but within the lysosome and endosome the pH is ∼5–6 (Zou et al., 2014 ; Mu et al., 2019 ). Thereby, U-SS-M may degrade in cell lysosome and endosome acidic condition.…”
Section: Resultsmentioning
confidence: 99%
“…The release of an encapsulated drug from a nanocarrier consisting of a liposome must increase local drug delivery while reducing the toxicity consequences of a temperature increase. [87][88][89][90] High-intensity focused ultrasound (HIFU), particularly micro-HIFU (MHIFU) microfluidic devices, allows us to imitate the bulky HIFU transmission tool with the help of lower power consumption and control the release of low temperature-sensitive liposomes (LTSL) investigated. 70,91 Furthermore, at the transition to a local temperature of between 41°C and 43°C, the structure changes from a gel to a liquid crystalline phase, releasing the encapsulated drugs with an external source of hyperthermia, such as microwaves, and an infrared radiation laser with the structure of a lipid membrane of low-temperature sensitive liposomes (LTSL).…”
Section: Synthesis Of Microfluidic Nanocarriersmentioning
confidence: 99%
“…Temperature is the most widespread stimulus to trigger the specific responsiveness of SAN for applications in cancer nanomedicine (Mu et al, 2019). Local temperature is slightly higher in solid tumors than in normal tissues; hence, nanocarriers may accumulate into the tumor by adjusting the thermoresponsiveness of ABC (phase transition temperature: upper or lower critical solution temperatures, UCST and LCST, respectively) (Ward and Georgiou, 2011) to be between body and tumor temperature (Onaca et al, 2009;Thambi et al, 2016;García, 2019b).…”
Section: Temperature-responsive Nanocarriersmentioning
confidence: 99%